2019
DOI: 10.3390/sym11020222
|View full text |Cite
|
Sign up to set email alerts
|

EasyStego: Robust Steganography Based on Quick-Response Barcodes for Crossing Domains

Abstract: Despite greater attention being paid to sensitive-information leakage in the cyberdomain, the sensitive-information problem of the physical domain remains neglected. Anonymous users can easily access the sensitive information of other users, such as transaction information, health status, and addresses, without any advanced technologies. Ideally, secret messages should be protected not only in the cyberdomain but also in the complex physical domain. However, popular steganography schemes only work in the tradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…From the graph, the PSNR value obtained for secret data is higher for all test images compared to the PSNR value for secret images. Secret messages should be protected not only in the cyber domain but also in the complex physical domain [23]. The results of Table 2 show that the proposed QR-based steganography method yields better results than all the existing techniques in almost all stenographic images.…”
Section: For Color Imagementioning
confidence: 98%
“…From the graph, the PSNR value obtained for secret data is higher for all test images compared to the PSNR value for secret images. Secret messages should be protected not only in the cyber domain but also in the complex physical domain [23]. The results of Table 2 show that the proposed QR-based steganography method yields better results than all the existing techniques in almost all stenographic images.…”
Section: For Color Imagementioning
confidence: 98%
“…However, this method is not robust against image compression. Luo et al [26] proposed EasyStego, a unique cross-domain steganography system. EasyStego is based on the usage of QR codes as carriers, therefore it is resistant to physical distortions in the complicated physical field.…”
Section: Related Workmentioning
confidence: 99%
“…Besides, the aforementioned, researchers found that the importance of reinforcing text steganography and cryptography methods lies in protecting the secret keys, which are considered the most critical element in information security technologies [35,37,149]. However, only a few researchers have used an encryption to improve the efficiency of their methods [150,151].…”
Section: Securitymentioning
confidence: 99%